Developing Realistic and Child-friendly Learning Model for Teaching Mathematics - Setyaningsih, Nining; Rejeki, Sri; Ishartono, Naufal (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
This study aims to develop a learning model based on the theory of realistic mathematics education and child-friendly learning for teaching mathematics in junior high school. This research is conducted using Plompâ€™s educational design research that consists of four development phases: 1) preliminary investigation, 2) designing, 3) realization, and 4) revision, evaluation. In addition, this study also tests the mathematics instructional model prototype being developed and validated by an expert. Based on the analysis, it can be concluded that: 1) the teacherâ€™s learning management in the implementation of realistic and child-friendly learning model can be classified â€œvery goodâ€, 2) the prototype model is categorized â€œvery goodâ€ in improving studentsâ€™ activities , and 3) the studentsâ€™ responses toward the developed mathematics instructional model are "positiveâ€. Moreover, the syntaxes of realistic and child-friendly learning model for teaching mathematics in junior high school have been formulated, namely: 1) explaining learning objectives and motivating students, 2) providing contextual problems students familiar with, or horizontal mathematization, 3) processing abstraction or vertical mathematization, 4) devising strategies, 5) communicating solution in a discussion, and 6) giving inferences of mathematics subject-matter.